A Research Agenda for Skills and Inequality - Tåhlin, Michael (Elgar Research Agendas, 2023)
Skills and inequality have long been a central theme in analyses of social structure and economic development. A Research Agenda for Skills and Inequality offers an insightful cross-disciplinary framework for research on how unequal living conditions form, persist and change in interplay with human skill formation and development.